Theory Matrix
theory Matrix
imports Main "HOL-Library.Lattice_Algebras"
begin
type_synonym 'a infmatrix = "nat ⇒ nat ⇒ 'a"
definition nonzero_positions :: "(nat ⇒ nat ⇒ 'a::zero) ⇒ (nat × nat) set" where
"nonzero_positions A = {pos. A (fst pos) (snd pos) ~= 0}"
definition "matrix = {(f::(nat ⇒ nat ⇒ 'a::zero)). finite (nonzero_positions f)}"
typedef (overloaded) 'a matrix = "matrix :: (nat ⇒ nat ⇒ 'a::zero) set"
unfolding matrix_def
proof
show "(λj i. 0) ∈ {(f::(nat ⇒ nat ⇒ 'a::zero)). finite (nonzero_positions f)}"
by (simp add: nonzero_positions_def)
qed
declare Rep_matrix_inverse[simp]
lemma matrix_eqI:
fixes A B :: "'a::zero matrix"
assumes "⋀m n. Rep_matrix A m n = Rep_matrix B m n"
shows "A=B"
using Rep_matrix_inject assms by blast
lemma finite_nonzero_positions : "finite (nonzero_positions (Rep_matrix A))"
by (induct A) (simp add: Abs_matrix_inverse matrix_def)
definition nrows :: "('a::zero) matrix ⇒ nat" where
"nrows A == if nonzero_positions(Rep_matrix A) = {} then 0 else Suc(Max ((image fst) (nonzero_positions (Rep_matrix A))))"
definition ncols :: "('a::zero) matrix ⇒ nat" where
"ncols A == if nonzero_positions(Rep_matrix A) = {} then 0 else Suc(Max ((image snd) (nonzero_positions (Rep_matrix A))))"
lemma nrows:
assumes hyp: "nrows A ≤ m"
shows "(Rep_matrix A m n) = 0"
proof cases
assume "nonzero_positions(Rep_matrix A) = {}"
then show "(Rep_matrix A m n) = 0" by (simp add: nonzero_positions_def)
next
assume a: "nonzero_positions(Rep_matrix A) ≠ {}"
let ?S = "fst`(nonzero_positions(Rep_matrix A))"
have c: "finite (?S)" by (simp add: finite_nonzero_positions)
from hyp have d: "Max (?S) < m" by (simp add: a nrows_def)
have "m ∉ ?S"
proof -
have "m ∈ ?S ⟹ m ≤ Max(?S)" by (simp add: Max_ge [OF c])
moreover from d have "~(m ≤ Max ?S)" by (simp)
ultimately show "m ∉ ?S" by (auto)
qed
thus "Rep_matrix A m n = 0" by (simp add: nonzero_positions_def image_Collect)
qed
definition transpose_infmatrix :: "'a infmatrix ⇒ 'a infmatrix" where
"transpose_infmatrix A j i == A i j"
definition transpose_matrix :: "('a::zero) matrix ⇒ 'a matrix" where
"transpose_matrix == Abs_matrix o transpose_infmatrix o Rep_matrix"
declare transpose_infmatrix_def[simp]
lemma transpose_infmatrix_twice[simp]: "transpose_infmatrix (transpose_infmatrix A) = A"
by ((rule ext)+, simp)
lemma transpose_infmatrix: "transpose_infmatrix (λj i. P j i) = (λj i. P i j)"
by force
lemma transpose_infmatrix_closed[simp]: "Rep_matrix (Abs_matrix (transpose_infmatrix (Rep_matrix x))) = transpose_infmatrix (Rep_matrix x)"
proof -
let ?A = "{pos. Rep_matrix x (snd pos) (fst pos) ≠ 0}"
let ?B = "{pos. Rep_matrix x (fst pos) (snd pos) ≠ 0}"
let ?swap = "λpos. (snd pos, fst pos)"
have "finite ?A"
proof -
have swap_image: "?swap`?A = ?B"
by (force simp add: image_def)
then have "finite (?swap`?A)"
by (metis (full_types) finite_nonzero_positions nonzero_positions_def)
moreover
have "inj_on ?swap ?A" by (simp add: inj_on_def)
ultimately show "finite ?A"
using finite_imageD by blast
qed
then show ?thesis
by (simp add: Abs_matrix_inverse matrix_def nonzero_positions_def)
qed
lemma infmatrixforward: "(x::'a infmatrix) = y ⟹ ∀ a b. x a b = y a b"
by auto
lemma transpose_infmatrix_inject: "(transpose_infmatrix A = transpose_infmatrix B) = (A = B)"
by (metis transpose_infmatrix_twice)
lemma transpose_matrix_inject: "(transpose_matrix A = transpose_matrix B) = (A = B)"
unfolding transpose_matrix_def o_def
by (metis Rep_matrix_inject transpose_infmatrix_closed transpose_infmatrix_inject)
lemma transpose_matrix[simp]: "Rep_matrix(transpose_matrix A) j i = Rep_matrix A i j"
by (simp add: transpose_matrix_def)
lemma transpose_transpose_id[simp]: "transpose_matrix (transpose_matrix A) = A"
by (simp add: transpose_matrix_def)
lemma nrows_transpose[simp]: "nrows (transpose_matrix A) = ncols A"
by (simp add: nrows_def ncols_def nonzero_positions_def transpose_matrix_def image_def)
lemma ncols_transpose[simp]: "ncols (transpose_matrix A) = nrows A"
by (metis nrows_transpose transpose_transpose_id)
lemma ncols: "ncols A ≤ n ⟹ Rep_matrix A m n = 0"
by (metis nrows nrows_transpose transpose_matrix)
lemma ncols_le: "(ncols A ≤ n) ⟷ (∀j i. n ≤ i ⟶ (Rep_matrix A j i) = 0)" (is "_ = ?st")
proof -
have "Rep_matrix A j i = 0"
if "ncols A ≤ n" "n ≤ i" for j i
by (meson that le_trans ncols)
moreover have "ncols A ≤ n"
if "∀j i. n ≤ i ⟶ Rep_matrix A j i = 0"
unfolding ncols_def
proof (clarsimp split: if_split_asm)
assume §: "nonzero_positions (Rep_matrix A) ≠ {}"
let ?P = "nonzero_positions (Rep_matrix A)"
let ?p = "snd`?P"
have a:"finite ?p" by (simp add: finite_nonzero_positions)
let ?m = "Max ?p"
show "Suc (Max (snd ` nonzero_positions (Rep_matrix A))) ≤ n"
using § that obtains_MAX [OF finite_nonzero_positions]
by (metis (mono_tags, lifting) mem_Collect_eq nonzero_positions_def not_less_eq_eq)
qed
ultimately show ?thesis
by auto
qed
lemma less_ncols: "(n < ncols A) = (∃j i. n ≤ i ∧ (Rep_matrix A j i) ≠ 0)"
by (meson linorder_not_le ncols_le)
lemma le_ncols: "(n ≤ ncols A) = (∀ m. (∀ j i. m ≤ i ⟶ (Rep_matrix A j i) = 0) ⟶ n ≤ m)"
by (meson le_trans ncols ncols_le)
lemma nrows_le: "(nrows A ≤ n) = (∀j i. n ≤ j ⟶ (Rep_matrix A j i) = 0)" (is ?s)
by (metis ncols_le ncols_transpose transpose_matrix)
lemma less_nrows: "(m < nrows A) = (∃j i. m ≤ j ∧ (Rep_matrix A j i) ≠ 0)"
by (meson linorder_not_le nrows_le)
lemma le_nrows: "(n ≤ nrows A) = (∀ m. (∀ j i. m ≤ j ⟶ (Rep_matrix A j i) = 0) ⟶ n ≤ m)"
by (meson order.trans nrows nrows_le)
lemma nrows_notzero: "Rep_matrix A m n ≠ 0 ⟹ m < nrows A"
by (meson leI nrows)
lemma ncols_notzero: "Rep_matrix A m n ≠ 0 ⟹ n < ncols A"
by (meson leI ncols)
lemma finite_natarray1: "finite {x. x < (n::nat)}"
by simp
lemma finite_natarray2: "finite {(x, y). x < (m::nat) ∧ y < (n::nat)}"
by simp
lemma RepAbs_matrix:
assumes "∃m. ∀j i. m ≤ j ⟶ x j i = 0"
and "∃n. ∀j i. (n ≤ i ⟶ x j i = 0)"
shows "(Rep_matrix (Abs_matrix x)) = x"
proof -
have "finite {pos. x (fst pos) (snd pos) ≠ 0}"
proof -
from assms obtain m n where a: "∀j i. m ≤ j ⟶ x j i = 0"
and b: "∀j i. n ≤ i ⟶ x j i = 0" by (blast)
let ?u = "{(i, j). x i j ≠ 0}"
let ?v = "{(i, j). i < m ∧ j < n}"
have c: "⋀(m::nat) a. ~(m ≤ a) ⟹ a < m" by (arith)
with a b have d: "?u ⊆ ?v" by blast
moreover have "finite ?v" by (simp add: finite_natarray2)
moreover have "{pos. x (fst pos) (snd pos) ≠ 0} = ?u" by auto
ultimately show "finite {pos. x (fst pos) (snd pos) ≠ 0}"
by (metis (lifting) finite_subset)
qed
then show ?thesis
by (simp add: Abs_matrix_inverse matrix_def nonzero_positions_def)
qed
definition apply_infmatrix :: "('a ⇒ 'b) ⇒ 'a infmatrix ⇒ 'b infmatrix" where
"apply_infmatrix f == λA. (λj i. f (A j i))"
definition apply_matrix :: "('a ⇒ 'b) ⇒ ('a::zero) matrix ⇒ ('b::zero) matrix" where
"apply_matrix f == λA. Abs_matrix (apply_infmatrix f (Rep_matrix A))"
definition combine_infmatrix :: "('a ⇒ 'b ⇒ 'c) ⇒ 'a infmatrix ⇒ 'b infmatrix ⇒ 'c infmatrix" where
"combine_infmatrix f == λA B. (λj i. f (A j i) (B j i))"
definition combine_matrix :: "('a ⇒ 'b ⇒ 'c) ⇒ ('a::zero) matrix ⇒ ('b::zero) matrix ⇒ ('c::zero) matrix" where
"combine_matrix f == λA B. Abs_matrix (combine_infmatrix f (Rep_matrix A) (Rep_matrix B))"
lemma expand_apply_infmatrix[simp]: "apply_infmatrix f A j i = f (A j i)"
by (simp add: apply_infmatrix_def)
lemma expand_combine_infmatrix[simp]: "combine_infmatrix f A B j i = f (A j i) (B j i)"
by (simp add: combine_infmatrix_def)
definition commutative :: "('a ⇒ 'a ⇒ 'b) ⇒ bool" where
"commutative f == ∀x y. f x y = f y x"
definition associative :: "('a ⇒ 'a ⇒ 'a) ⇒ bool" where
"associative f == ∀x y z. f (f x y) z = f x (f y z)"
text‹
To reason about associativity and commutativity of operations on matrices,
let's take a step back and look at the general situtation: Assume that we have
sets $A$ and $B$ with $B \subset A$ and an abstraction $u: A \rightarrow B$. This abstraction has to fulfill $u(b) = b$ for all $b \in B$, but is arbitrary otherwise.
Each function $f: A \times A \rightarrow A$ now induces a function $f': B \times B \rightarrow B$ by $f' = u \circ f$.
It is obvious that commutativity of $f$ implies commutativity of $f'$: $f' x y = u (f x y) = u (f y x) = f' y x.$
›
lemma combine_infmatrix_commute:
"commutative f ⟹ commutative (combine_infmatrix f)"
by (simp add: commutative_def combine_infmatrix_def)
lemma combine_matrix_commute:
"commutative f ⟹ commutative (combine_matrix f)"
by (simp add: combine_matrix_def commutative_def combine_infmatrix_def)
text‹
On the contrary, given an associative function $f$ we cannot expect $f'$ to be associative. A counterexample is given by $A=\bbbZ$, $B=\{-1, 0, 1\}$,
as $f$ we take addition on $\bbbZ$, which is clearly associative. The abstraction is given by $u(a) = 0$ for $a \notin B$. Then we have
\[ f' (f' 1 1) -1 = u(f (u (f 1 1)) -1) = u(f (u 2) -1) = u (f 0 -1) = -1, \]
but on the other hand we have
\[ f' 1 (f' 1 -1) = u (f 1 (u (f 1 -1))) = u (f 1 0) = 1.\]
A way out of this problem is to assume that $f(A\times A)\subset A$ holds, and this is what we are going to do:
›
lemma nonzero_positions_combine_infmatrix[simp]: "f 0 0 = 0 ⟹ nonzero_positions (combine_infmatrix f A B) ⊆ (nonzero_positions A) ∪ (nonzero_positions B)"
by (smt (verit) UnCI expand_combine_infmatrix mem_Collect_eq nonzero_positions_def subsetI)
lemma finite_nonzero_positions_Rep[simp]: "finite (nonzero_positions (Rep_matrix A))"
by (simp add: finite_nonzero_positions)
lemma combine_infmatrix_closed [simp]:
"f 0 0 = 0 ⟹ Rep_matrix (Abs_matrix (combine_infmatrix f (Rep_matrix A) (Rep_matrix B))) = combine_infmatrix f (Rep_matrix A) (Rep_matrix B)"
apply (rule Abs_matrix_inverse)
apply (simp add: matrix_def)
by (meson finite_Un finite_nonzero_positions_Rep finite_subset nonzero_positions_combine_infmatrix)
text ‹We need the next two lemmas only later, but it is analog to the above one, so we prove them now:›
lemma nonzero_positions_apply_infmatrix[simp]: "f 0 = 0 ⟹ nonzero_positions (apply_infmatrix f A) ⊆ nonzero_positions A"
by (rule subsetI, simp add: nonzero_positions_def apply_infmatrix_def, auto)
lemma apply_infmatrix_closed [simp]:
"f 0 = 0 ⟹ Rep_matrix (Abs_matrix (apply_infmatrix f (Rep_matrix A))) = apply_infmatrix f (Rep_matrix A)"
apply (rule Abs_matrix_inverse)
apply (simp add: matrix_def)
by (meson finite_nonzero_positions_Rep finite_subset nonzero_positions_apply_infmatrix)
lemma combine_infmatrix_assoc[simp]: "f 0 0 = 0 ⟹ associative f ⟹ associative (combine_infmatrix f)"
by (simp add: associative_def combine_infmatrix_def)
lemma combine_matrix_assoc: "f 0 0 = 0 ⟹ associative f ⟹ associative (combine_matrix f)"
by (smt (verit) associative_def combine_infmatrix_assoc combine_infmatrix_closed combine_matrix_def)
lemma Rep_apply_matrix[simp]: "f 0 = 0 ⟹ Rep_matrix (apply_matrix f A) j i = f (Rep_matrix A j i)"
by (simp add: apply_matrix_def)
lemma Rep_combine_matrix[simp]: "f 0 0 = 0 ⟹ Rep_matrix (combine_matrix f A B) j i = f (Rep_matrix A j i) (Rep_matrix B j i)"
by(simp add: combine_matrix_def)
lemma combine_nrows_max: "f 0 0 = 0 ⟹ nrows (combine_matrix f A B) ≤ max (nrows A) (nrows B)"
by (simp add: nrows_le)
lemma combine_ncols_max: "f 0 0 = 0 ⟹ ncols (combine_matrix f A B) ≤ max (ncols A) (ncols B)"
by (simp add: ncols_le)
lemma combine_nrows: "f 0 0 = 0 ⟹ nrows A ≤ q ⟹ nrows B ≤ q ⟹ nrows(combine_matrix f A B) ≤ q"
by (simp add: nrows_le)
lemma combine_ncols: "f 0 0 = 0 ⟹ ncols A ≤ q ⟹ ncols B ≤ q ⟹ ncols(combine_matrix f A B) ≤ q"
by (simp add: ncols_le)
definition zero_r_neutral :: "('a ⇒ 'b::zero ⇒ 'a) ⇒ bool" where
"zero_r_neutral f == ∀a. f a 0 = a"
definition zero_l_neutral :: "('a::zero ⇒ 'b ⇒ 'b) ⇒ bool" where
"zero_l_neutral f == ∀a. f 0 a = a"
definition zero_closed :: "(('a::zero) ⇒ ('b::zero) ⇒ ('c::zero)) ⇒ bool" where
"zero_closed f == (∀x. f x 0 = 0) ∧ (∀y. f 0 y = 0)"
primrec foldseq :: "('a ⇒ 'a ⇒ 'a) ⇒ (nat ⇒ 'a) ⇒ nat ⇒ 'a"
where
"foldseq f s 0 = s 0"
| "foldseq f s (Suc n) = f (s 0) (foldseq f (λk. s(Suc k)) n)"
primrec foldseq_transposed :: "('a ⇒ 'a ⇒ 'a) ⇒ (nat ⇒ 'a) ⇒ nat ⇒ 'a"
where
"foldseq_transposed f s 0 = s 0"
| "foldseq_transposed f s (Suc n) = f (foldseq_transposed f s n) (s (Suc n))"
lemma foldseq_assoc:
assumes a:"associative f"
shows "associative f ⟹ foldseq f = foldseq_transposed f"
proof -
have "N ≤ n ⟹ foldseq f s N = foldseq_transposed f s N" for N s n
proof (induct n arbitrary: N s)
case 0
then show ?case
by auto
next
case (Suc n)
show ?case
proof cases
assume "N ≤ n"
then show ?thesis
by (simp add: Suc.hyps)
next
assume "~(N ≤ n)"
then have Nsuceq: "N = Suc n"
using Suc.prems by linarith
have neqz: "n ≠ 0 ⟹ ∃m. n = Suc m ∧ Suc m ≤ n"
by arith
have assocf: "!! x y z. f x (f y z) = f (f x y) z"
by (metis a associative_def)
have "f (f (s 0) (foldseq_transposed f (λk. s (Suc k)) m)) (s (Suc (Suc m))) =
f (f (foldseq_transposed f s m) (s (Suc m))) (s (Suc (Suc m)))"
if "n = Suc m" for m
proof -
have §: "foldseq_transposed f (λk. s (Suc k)) m = foldseq f (λk. s (Suc k)) m" (is "?T1 = ?T2")
by (simp add: Suc.hyps that)
have "f (s 0) ?T2 = foldseq f s (Suc m)" by simp
also have "… = foldseq_transposed f s (Suc m)"
using Suc.hyps that by blast
also have "… = f (foldseq_transposed f s m) (s (Suc m))"
by simp
finally show ?thesis
by (simp add: §)
qed
then show "foldseq f s N = foldseq_transposed f s N"
unfolding Nsuceq using assocf Suc.hyps neqz by force
qed
qed
then show ?thesis
by blast
qed
lemma foldseq_distr:
assumes assoc: "associative f" and comm: "commutative f"
shows "foldseq f (λk. f (u k) (v k)) n = f (foldseq f u n) (foldseq f v n)"
proof -
from assoc have a:"!! x y z. f (f x y) z = f x (f y z)" by (simp add: associative_def)
from comm have b: "!! x y. f x y = f y x" by (simp add: commutative_def)
from assoc comm have c: "!! x y z. f x (f y z) = f y (f x z)" by (simp add: commutative_def associative_def)
have "(∀u v. foldseq f (λk. f (u k) (v k)) n = f (foldseq f u n) (foldseq f v n))" for n
by (induct n) (simp_all add: assoc b c foldseq_assoc)
then show "foldseq f (λk. f (u k) (v k)) n = f (foldseq f u n) (foldseq f v n)" by simp
qed
theorem "⟦associative f; associative g; ∀a b c d. g (f a b) (f c d) = f (g a c) (g b d); ∃x y. (f x) ≠ (f y); ∃x y. (g x) ≠ (g y); f x x = x; g x x = x⟧ ⟹ f=g | (∀y. f y x = y) | (∀y. g y x = y)"
oops
lemma foldseq_zero:
assumes fz: "f 0 0 = 0" and sz: "∀i. i ≤ n ⟶ s i = 0"
shows "foldseq f s n = 0"
proof -
have "∀s. (∀i. i ≤ n ⟶ s i = 0) ⟶ foldseq f s n = 0" for n
by (induct n) (simp_all add: fz)
then show ?thesis
by (simp add: sz)
qed
lemma foldseq_significant_positions:
assumes p: "∀i. i ≤ N ⟶ S i = T i"
shows "foldseq f S N = foldseq f T N"
using assms
proof (induction N arbitrary: S T)
case 0
then show ?case by simp
next
case (Suc N)
then show ?case
unfolding foldseq.simps by (metis not_less_eq_eq le0)
qed
lemma foldseq_tail:
assumes "M ≤ N"
shows "foldseq f S N = foldseq f (λk. (if k < M then (S k) else (foldseq f (λk. S(k+M)) (N-M)))) M"
using assms
proof (induction N arbitrary: M S)
case 0
then show ?case by auto
next
case (Suc N)
show ?case
proof (cases "M = Suc N")
case True
then show ?thesis
by (auto intro!: arg_cong [of concl: "f (S 0)"] foldseq_significant_positions)
next
case False
then have "M≤N"
using Suc.prems by force
show ?thesis
proof (cases "M = 0")
case True
then show ?thesis
by auto
next
case False
then obtain M' where M': "M = Suc M'" "M' ≤ N"
by (metis Suc_leD ‹M ≤ N› nat.nchotomy)
then show ?thesis
apply (simp add: Suc.IH [OF ‹M'≤N›])
using add_Suc_right diff_Suc_Suc by presburger
qed
qed
qed
lemma foldseq_zerotail:
assumes fz: "f 0 0 = 0" and sz: "∀i. n ≤ i ⟶ s i = 0" and nm: "n ≤ m"
shows "foldseq f s n = foldseq f s m"
unfolding foldseq_tail[OF nm]
by (metis (no_types, lifting) foldseq_zero fz le_add2 linorder_not_le sz)
lemma foldseq_zerotail2:
assumes "∀x. f x 0 = x"
and "∀i. n < i ⟶ s i = 0"
and nm: "n ≤ m"
shows "foldseq f s n = foldseq f s m"
proof -
have "s i = (if i < n then s i else foldseq f (λk. s (k + n)) (m - n))"
if "i≤n" for i
proof (cases "m=n")
case True
then show ?thesis
using that by auto
next
case False
then obtain k where "m-n = Suc k"
by (metis Suc_diff_Suc le_neq_implies_less nm)
then show ?thesis
apply simp
by (simp add: assms(1,2) foldseq_zero nat_less_le that)
qed
then show ?thesis
unfolding foldseq_tail[OF nm]
by (auto intro: foldseq_significant_positions)
qed
lemma foldseq_zerostart:
assumes f00x: "∀x. f 0 (f 0 x) = f 0 x" and 0: "∀i. i ≤ n ⟶ s i = 0"
shows "foldseq f s (Suc n) = f 0 (s (Suc n))"
using 0
proof (induction n arbitrary: s)
case 0
then show ?case by auto
next
case (Suc n s)
then show ?case
apply (simp add: le_Suc_eq)
by (smt (verit, ccfv_threshold) Suc.prems Suc_le_mono f00x foldseq_significant_positions le0)
qed
lemma foldseq_zerostart2:
assumes x: "∀x. f 0 x = x" and 0: "∀i. i < n ⟶ s i = 0"
shows "foldseq f s n = s n"
proof -
show "foldseq f s n = s n"
proof (cases n)
case 0
then show ?thesis
by auto
next
case (Suc n')
then show ?thesis
by (metis "0" foldseq_zerostart le_imp_less_Suc x)
qed
qed
lemma foldseq_almostzero:
assumes f0x: "∀x. f 0 x = x" and fx0: "∀x. f x 0 = x" and s0: "∀i. i ≠ j ⟶ s i = 0"
shows "foldseq f s n = (if (j ≤ n) then (s j) else 0)"
by (smt (verit, ccfv_SIG) f0x foldseq_zerostart2 foldseq_zerotail2 fx0 le_refl nat_less_le s0)
lemma foldseq_distr_unary:
assumes "⋀a b. g (f a b) = f (g a) (g b)"
shows "g(foldseq f s n) = foldseq f (λx. g(s x)) n"
proof (induction n arbitrary: s)
case 0
then show ?case
by auto
next
case (Suc n)
then show ?case
using assms by fastforce
qed
definition mult_matrix_n :: "nat ⇒ (('a::zero) ⇒ ('b::zero) ⇒ ('c::zero)) ⇒ ('c ⇒ 'c ⇒ 'c) ⇒ 'a matrix ⇒ 'b matrix ⇒ 'c matrix" where
"mult_matrix_n n fmul fadd A B == Abs_matrix(λj i. foldseq fadd (λk. fmul (Rep_matrix A j k) (Rep_matrix B k i)) n)"
definition mult_matrix :: "(('a::zero) ⇒ ('b::zero) ⇒ ('c::zero)) ⇒ ('c ⇒ 'c ⇒ 'c) ⇒ 'a matrix ⇒ 'b matrix ⇒ 'c matrix" where
"mult_matrix fmul fadd A B == mult_matrix_n (max (ncols A) (nrows B)) fmul fadd A B"
lemma mult_matrix_n:
assumes "ncols A ≤ n" "nrows B ≤ n" "fadd 0 0 = 0" "fmul 0 0 = 0"
shows "mult_matrix fmul fadd A B = mult_matrix_n n fmul fadd A B"
proof -
have "foldseq fadd (λk. fmul (Rep_matrix A j k) (Rep_matrix B k i))
(max (ncols A) (nrows B)) =
foldseq fadd (λk. fmul (Rep_matrix A j k) (Rep_matrix B k i)) n" for i j
using assms by (simp add: foldseq_zerotail nrows_le ncols_le)
then show ?thesis
by (simp add: mult_matrix_def mult_matrix_n_def)
qed
lemma mult_matrix_nm:
assumes "ncols A ≤ n" "nrows B ≤ n" "ncols A ≤ m" "nrows B ≤ m" "fadd 0 0 = 0" "fmul 0 0 = 0"
shows "mult_matrix_n n fmul fadd A B = mult_matrix_n m fmul fadd A B"
proof -
from assms have "mult_matrix_n n fmul fadd A B = mult_matrix fmul fadd A B"
by (simp add: mult_matrix_n)
also from assms have "… = mult_matrix_n m fmul fadd A B"
by (simp add: mult_matrix_n[THEN sym])
finally show "mult_matrix_n n fmul fadd A B = mult_matrix_n m fmul fadd A B" by simp
qed
definition r_distributive :: "('a ⇒ 'b ⇒ 'b) ⇒ ('b ⇒ 'b ⇒ 'b) ⇒ bool" where
"r_distributive fmul fadd == ∀a u v. fmul a (fadd u v) = fadd (fmul a u) (fmul a v)"
definition l_distributive :: "('a ⇒ 'b ⇒ 'a) ⇒ ('a ⇒ 'a ⇒ 'a) ⇒ bool" where
"l_distributive fmul fadd == ∀a u v. fmul (fadd u v) a = fadd (fmul u a) (fmul v a)"
definition distributive :: "('a ⇒ 'a ⇒ 'a) ⇒ ('a ⇒ 'a ⇒ 'a) ⇒ bool" where
"distributive fmul fadd == l_distributive fmul fadd ∧ r_distributive fmul fadd"
lemma max1: "!! a x y. (a::nat) ≤ x ⟹ a ≤ max x y" by (arith)
lemma max2: "!! b x y. (b::nat) ≤ y ⟹ b ≤ max x y" by (arith)
lemma r_distributive_matrix:
assumes
"r_distributive fmul fadd"
"associative fadd"
"commutative fadd"
"fadd 0 0 = 0"
"∀a. fmul a 0 = 0"
"∀a. fmul 0 a = 0"
shows "r_distributive (mult_matrix fmul fadd) (combine_matrix fadd)"
proof -
from assms show ?thesis
apply (simp add: r_distributive_def mult_matrix_def, auto)
proof -
fix a::"'a matrix"
fix u::"'b matrix"
fix v::"'b matrix"
let ?mx = "max (ncols a) (max (nrows u) (nrows v))"
from assms show "mult_matrix_n (max (ncols a) (nrows (combine_matrix fadd u v))) fmul fadd a (combine_matrix fadd u v) =
combine_matrix fadd (mult_matrix_n (max (ncols a) (nrows u)) fmul fadd a u) (mult_matrix_n (max (ncols a) (nrows v)) fmul fadd a v)"
apply (subst mult_matrix_nm[of _ _ _ ?mx fadd fmul])
apply (simp add: max1 max2 combine_nrows combine_ncols)+
apply (subst mult_matrix_nm[of _ _ v ?mx fadd fmul])
apply (simp add: max1 max2 combine_nrows combine_ncols)+
apply (subst mult_matrix_nm[of _ _ u ?mx fadd fmul])
apply (simp add: max1 max2 combine_nrows combine_ncols)+
apply (simp add: mult_matrix_n_def r_distributive_def foldseq_distr[of fadd])
apply (simp add: combine_matrix_def combine_infmatrix_def)
apply (intro ext arg_cong[of concl: "Abs_matrix"])
apply (simplesubst RepAbs_matrix)
apply (simp, auto)
apply (rule exI[of _ "nrows a"], simp add: nrows_le foldseq_zero)
apply (rule exI[of _ "ncols v"], simp add: ncols_le foldseq_zero)
apply (subst RepAbs_matrix)
apply (simp, auto)
apply (rule exI[of _ "nrows a"], simp add: nrows_le foldseq_zero)
apply (rule exI[of _ "ncols u"], simp add: ncols_le foldseq_zero)
done
qed
qed
lemma l_distributive_matrix:
assumes
"l_distributive fmul fadd"
"associative fadd"
"commutative fadd"
"fadd 0 0 = 0"
"∀a. fmul a 0 = 0"
"∀a. fmul 0 a = 0"
shows "l_distributive (mult_matrix fmul fadd) (combine_matrix fadd)"
proof -
from assms show ?thesis
apply (simp add: l_distributive_def mult_matrix_def, auto)
proof -
fix a::"'b matrix"
fix u::"'a matrix"
fix v::"'a matrix"
let ?mx = "max (nrows a) (max (ncols u) (ncols v))"
from assms show "mult_matrix_n (max (ncols (combine_matrix fadd u v)) (nrows a)) fmul fadd (combine_matrix fadd u v) a =
combine_matrix fadd (mult_matrix_n (max (ncols u) (nrows a)) fmul fadd u a) (mult_matrix_n (max (ncols v) (nrows a)) fmul fadd v a)"
apply (subst mult_matrix_nm[of v _ _ ?mx fadd fmul])
apply (simp add: max1 max2 combine_nrows combine_ncols)+
apply (subst mult_matrix_nm[of u _ _ ?mx fadd fmul])
apply (simp add: max1 max2 combine_nrows combine_ncols)+
apply (subst mult_matrix_nm[of _ _ _ ?mx fadd fmul])
apply (simp add: max1 max2 combine_nrows combine_ncols)+
apply (simp add: mult_matrix_n_def l_distributive_def foldseq_distr[of fadd])
apply (simp add: combine_matrix_def combine_infmatrix_def)
apply (intro ext arg_cong[of concl: "Abs_matrix"])
apply (simplesubst RepAbs_matrix)
apply (simp, auto)
apply (rule exI[of _ "nrows v"], simp add: nrows_le foldseq_zero)
apply (rule exI[of _ "ncols a"], simp add: ncols_le foldseq_zero)
apply (subst RepAbs_matrix)
apply (simp, auto)
apply (rule exI[of _ "nrows u"], simp add: nrows_le foldseq_zero)
apply (rule exI[of _ "ncols a"], simp add: ncols_le foldseq_zero)
done
qed
qed
instantiation matrix :: (zero) zero
begin
definition zero_matrix_def: "0 = Abs_matrix (λj i. 0)"
instance ..
end
lemma Rep_zero_matrix_def[simp]: "Rep_matrix 0 j i = 0"
by (simp add: RepAbs_matrix zero_matrix_def)
lemma zero_matrix_def_nrows[simp]: "nrows 0 = 0"
using nrows_le by force
lemma zero_matrix_def_ncols[simp]: "ncols 0 = 0"
using ncols_le by fastforce
lemma combine_matrix_zero_l_neutral: "zero_l_neutral f ⟹ zero_l_neutral (combine_matrix f)"
by (simp add: zero_l_neutral_def combine_matrix_def combine_infmatrix_def)
lemma combine_matrix_zero_r_neutral: "zero_r_neutral f ⟹ zero_r_neutral (combine_matrix f)"
by (simp add: zero_r_neutral_def combine_matrix_def combine_infmatrix_def)
lemma mult_matrix_zero_closed: "⟦fadd 0 0 = 0; zero_closed fmul⟧ ⟹ zero_closed (mult_matrix fmul fadd)"
apply (simp add: zero_closed_def mult_matrix_def mult_matrix_n_def)
by (simp add: foldseq_zero zero_matrix_def)
lemma mult_matrix_n_zero_right[simp]: "⟦fadd 0 0 = 0; ∀a. fmul a 0 = 0⟧ ⟹ mult_matrix_n n fmul fadd A 0 = 0"
by (simp add: RepAbs_matrix foldseq_zero matrix_eqI mult_matrix_n_def)
lemma mult_matrix_n_zero_left[simp]: "⟦fadd 0 0 = 0; ∀a. fmul 0 a = 0⟧ ⟹ mult_matrix_n n fmul fadd 0 A = 0"
by (simp add: RepAbs_matrix foldseq_zero matrix_eqI mult_matrix_n_def)
lemma mult_matrix_zero_left[simp]: "⟦fadd 0 0 = 0; ∀a. fmul 0 a = 0⟧ ⟹ mult_matrix fmul fadd 0 A = 0"
by (simp add: mult_matrix_def)
lemma mult_matrix_zero_right[simp]: "⟦fadd 0 0 = 0; ∀a. fmul a 0 = 0⟧ ⟹ mult_matrix fmul fadd A 0 = 0"
by (simp add: mult_matrix_def)
lemma apply_matrix_zero[simp]: "f 0 = 0 ⟹ apply_matrix f 0 = 0"
by (simp add: matrix_eqI)
lemma combine_matrix_zero: "f 0 0 = 0 ⟹ combine_matrix f 0 0 = 0"
by (simp add: matrix_eqI)
lemma transpose_matrix_zero[simp]: "transpose_matrix 0 = 0"
by (simp add: matrix_eqI)
lemma apply_zero_matrix_def[simp]: "apply_matrix (λx. 0) A = 0"
by (simp add: matrix_eqI)
definition singleton_matrix :: "nat ⇒ nat ⇒ ('a::zero) ⇒ 'a matrix" where
"singleton_matrix j i a == Abs_matrix(λm n. if j = m ∧ i = n then a else 0)"
definition move_matrix :: "('a::zero) matrix ⇒ int ⇒ int ⇒ 'a matrix" where
"move_matrix A y x == Abs_matrix(λj i. if (((int j)-y) < 0) | (((int i)-x) < 0) then 0 else Rep_matrix A (nat ((int j)-y)) (nat ((int i)-x)))"
definition take_rows :: "('a::zero) matrix ⇒ nat ⇒ 'a matrix" where
"take_rows A r == Abs_matrix(λj i. if (j < r) then (Rep_matrix A j i) else 0)"
definition take_columns :: "('a::zero) matrix ⇒ nat ⇒ 'a matrix" where
"take_columns A c == Abs_matrix(λj i. if (i < c) then (Rep_matrix A j i) else 0)"
definition column_of_matrix :: "('a::zero) matrix ⇒ nat ⇒ 'a matrix" where
"column_of_matrix A n == take_columns (move_matrix A 0 (- int n)) 1"
definition row_of_matrix :: "('a::zero) matrix ⇒ nat ⇒ 'a matrix" where
"row_of_matrix A m == take_rows (move_matrix A (- int m) 0) 1"
lemma Rep_singleton_matrix[simp]: "Rep_matrix (singleton_matrix j i e) m n = (if j = m ∧ i = n then e else 0)"
unfolding singleton_matrix_def
by (smt (verit, del_insts) RepAbs_matrix Suc_n_not_le_n)
lemma apply_singleton_matrix[simp]: "f 0 = 0 ⟹ apply_matrix f (singleton_matrix j i x) = (singleton_matrix j i (f x))"
by (simp add: matrix_eqI)
lemma singleton_matrix_zero[simp]: "singleton_matrix j i 0 = 0"
by (simp add: singleton_matrix_def zero_matrix_def)
lemma nrows_singleton[simp]: "nrows(singleton_matrix j i e) = (if e = 0 then 0 else Suc j)"
proof -
have "e ≠ 0 ⟹ Suc j ≤ nrows (singleton_matrix j i e)"
by (metis Rep_singleton_matrix not_less_eq_eq nrows)
then show ?thesis
by (simp add: le_antisym nrows_le)
qed
lemma ncols_singleton[simp]: "ncols(singleton_matrix j i e) = (if e = 0 then 0 else Suc i)"
by (simp add: Suc_leI le_antisym ncols_le ncols_notzero)
lemma combine_singleton: "f 0 0 = 0 ⟹ combine_matrix f (singleton_matrix j i a) (singleton_matrix j i b) = singleton_matrix j i (f a b)"
apply (simp add: singleton_matrix_def combine_matrix_def combine_infmatrix_def)
apply (intro ext arg_cong[of concl: "Abs_matrix"])
by (metis Rep_singleton_matrix singleton_matrix_def)
lemma transpose_singleton[simp]: "transpose_matrix (singleton_matrix j i a) = singleton_matrix i j a"
by (simp add: matrix_eqI)
lemma Rep_move_matrix[simp]:
"Rep_matrix (move_matrix A y x) j i =
(if (((int j)-y) < 0) | (((int i)-x) < 0) then 0 else Rep_matrix A (nat((int j)-y)) (nat((int i)-x)))"
apply (simp add: move_matrix_def)
by (subst RepAbs_matrix,
rule exI[of _ "(nrows A)+(nat ¦y¦)"], auto, rule nrows, arith,
rule exI[of _ "(ncols A)+(nat ¦x¦)"], auto, rule ncols, arith)+
lemma move_matrix_0_0[simp]: "move_matrix A 0 0 = A"
by (simp add: move_matrix_def)
lemma move_matrix_ortho: "move_matrix A j i = move_matrix (move_matrix A j 0) 0 i"
by (simp add: matrix_eqI)
lemma transpose_move_matrix[simp]:
"transpose_matrix (move_matrix A x y) = move_matrix (transpose_matrix A) y x"
by (simp add: matrix_eqI)
lemma move_matrix_singleton[simp]: "move_matrix (singleton_matrix u v x) j i =
(if (j + int u < 0) | (i + int v < 0) then 0 else (singleton_matrix (nat (j + int u)) (nat (i + int v)) x))"
by (auto intro!: matrix_eqI split: if_split_asm)
lemma Rep_take_columns[simp]:
"Rep_matrix (take_columns A c) j i = (if i < c then (Rep_matrix A j i) else 0)"
unfolding take_columns_def
by (smt (verit, best) RepAbs_matrix leD nrows)
lemma Rep_take_rows[simp]:
"Rep_matrix (take_rows A r) j i = (if j < r then (Rep_matrix A j i) else 0)"
unfolding take_rows_def
by (smt (verit, best) RepAbs_matrix leD ncols)
lemma Rep_column_of_matrix[simp]:
"Rep_matrix (column_of_matrix A c) j i = (if i = 0 then (Rep_matrix A j c) else 0)"
by (simp add: column_of_matrix_def)
lemma Rep_row_of_matrix[simp]:
"Rep_matrix (row_of_matrix A r) j i = (if j = 0 then (Rep_matrix A r i) else 0)"
by (simp add: row_of_matrix_def)
lemma column_of_matrix: "ncols A ≤ n ⟹ column_of_matrix A n = 0"
by (simp add: matrix_eqI ncols)
lemma row_of_matrix: "nrows A ≤ n ⟹ row_of_matrix A n = 0"
by (simp add: matrix_eqI nrows)
lemma mult_matrix_singleton_right[simp]:
assumes "∀x. fmul x 0 = 0" "∀x. fmul 0 x = 0" "∀x. fadd 0 x = x" "∀x. fadd x 0 = x"
shows "(mult_matrix fmul fadd A (singleton_matrix j i e)) = apply_matrix (λx. fmul x e) (move_matrix (column_of_matrix A j) 0 (int i))"
using assms
unfolding mult_matrix_def
apply (subst mult_matrix_nm[of _ _ _ "max (ncols A) (Suc j)"];
simp add: mult_matrix_n_def apply_matrix_def apply_infmatrix_def)
apply (intro ext arg_cong[of concl: "Abs_matrix"])
by (simp add: max_def assms foldseq_almostzero[of _ j])
lemma mult_matrix_ext:
assumes
eprem:
"∃e. (∀a b. a ≠ b ⟶ fmul a e ≠ fmul b e)"
and fprems:
"∀a. fmul 0 a = 0"
"∀a. fmul a 0 = 0"
"∀a. fadd a 0 = a"
"∀a. fadd 0 a = a"
and contraprems: "mult_matrix fmul fadd A = mult_matrix fmul fadd B"
shows "A = B"
proof(rule ccontr)
assume "A ≠ B"
then obtain J I where ne: "(Rep_matrix A J I) ≠ (Rep_matrix B J I)"
by (meson matrix_eqI)
from eprem obtain e where eprops:"(∀a b. a ≠ b ⟶ fmul a e ≠ fmul b e)" by blast
let ?S = "singleton_matrix I 0 e"
let ?comp = "mult_matrix fmul fadd"
have d: "!!x f g. f = g ⟹ f x = g x" by blast
have e: "(λx. fmul x e) 0 = 0" by (simp add: assms)
have "Rep_matrix (apply_matrix (λx. fmul x e) (column_of_matrix A I)) ≠
Rep_matrix (apply_matrix (λx. fmul x e) (column_of_matrix B I))"
using fprems
by (metis Rep_apply_matrix Rep_column_of_matrix eprops ne)
then have "?comp A ?S ≠ ?comp B ?S"
by (simp add: fprems eprops Rep_matrix_inject)
with contraprems show "False" by simp
qed
definition foldmatrix :: "('a ⇒ 'a ⇒ 'a) ⇒ ('a ⇒ 'a ⇒ 'a) ⇒ ('a infmatrix) ⇒ nat ⇒ nat ⇒ 'a" where
"foldmatrix f g A m n == foldseq_transposed g (λj. foldseq f (A j) n) m"
definition foldmatrix_transposed :: "('a ⇒ 'a ⇒ 'a) ⇒ ('a ⇒ 'a ⇒ 'a) ⇒ ('a infmatrix) ⇒ nat ⇒ nat ⇒ 'a" where
"foldmatrix_transposed f g A m n == foldseq g (λj. foldseq_transposed f (A j) n) m"
lemma foldmatrix_transpose:
assumes "∀a b c d. g(f a b) (f c d) = f (g a c) (g b d)"
shows "foldmatrix f g A m n = foldmatrix_transposed g f (transpose_infmatrix A) n m"
proof -
have forall:"⋀P x. (∀x. P x) ⟹ P x" by auto
have tworows:"∀A. foldmatrix f g A 1 n = foldmatrix_transposed g f (transpose_infmatrix A) n 1"
proof (induct n)
case 0
then show ?case
by (simp add: foldmatrix_def foldmatrix_transposed_def)
next
case (Suc n)
then show ?case
apply (clarsimp simp: foldmatrix_def foldmatrix_transposed_def assms)
apply (rule arg_cong [of concl: "f _"])
by meson
qed
have "foldseq_transposed g (λj. foldseq f (A j) n) m =
foldseq f (λj. foldseq_transposed g (transpose_infmatrix A j) m) n"
proof (induct m)
case 0
then show ?case by auto
next
case (Suc m)
then show ?case
using tworows
apply (drule_tac x="λj i. (if j = 0 then (foldseq_transposed g (λu. A u i) m) else (A (Suc m) i))" in spec)
by (simp add: Suc foldmatrix_def foldmatrix_transposed_def)
qed
then show "foldmatrix f g A m n = foldmatrix_transposed g f (transpose_infmatrix A) n m"
by (simp add: foldmatrix_def foldmatrix_transposed_def)
qed
lemma foldseq_foldseq:
assumes "associative f" "associative g" "∀a b c d. g(f a b) (f c d) = f (g a c) (g b d)"
shows
"foldseq g (λj. foldseq f (A j) n) m = foldseq f (λj. foldseq g ((transpose_infmatrix A) j) m) n"
using foldmatrix_transpose[of g f A m n]
by (simp add: foldmatrix_def foldmatrix_transposed_def foldseq_assoc[THEN sym] assms)
lemma mult_n_nrows:
assumes "∀a. fmul 0 a = 0" "∀a. fmul a 0 = 0" "fadd 0 0 = 0"
shows "nrows (mult_matrix_n n fmul fadd A B) ≤ nrows A"
unfolding nrows_le mult_matrix_n_def
apply (subst RepAbs_matrix)
apply (rule_tac x="nrows A" in exI)
apply (simp add: nrows assms foldseq_zero)
apply (rule_tac x="ncols B" in exI)
apply (simp add: ncols assms foldseq_zero)
apply (simp add: nrows assms foldseq_zero)
done
lemma mult_n_ncols:
assumes "∀a. fmul 0 a = 0" "∀a. fmul a 0 = 0" "fadd 0 0 = 0"
shows "ncols (mult_matrix_n n fmul fadd A B) ≤ ncols B"
unfolding ncols_le mult_matrix_n_def
apply (subst RepAbs_matrix)
apply (rule_tac x="nrows A" in exI)
apply (simp add: nrows assms foldseq_zero)
apply (rule_tac x="ncols B" in exI)
apply (simp add: ncols assms foldseq_zero)
apply (simp add: ncols assms foldseq_zero)
done
lemma mult_nrows:
assumes
"∀a. fmul 0 a = 0"
"∀a. fmul a 0 = 0"
"fadd 0 0 = 0"
shows "nrows (mult_matrix fmul fadd A B) ≤ nrows A"
by (simp add: mult_matrix_def mult_n_nrows assms)
lemma mult_ncols:
assumes
"∀a. fmul 0 a = 0"
"∀a. fmul a 0 = 0"
"fadd 0 0 = 0"
shows "ncols (mult_matrix fmul fadd A B) ≤ ncols B"
by (simp add: mult_matrix_def mult_n_ncols assms)
lemma nrows_move_matrix_le: "nrows (move_matrix A j i) ≤ nat((int (nrows A)) + j)"
by (smt (verit) Rep_move_matrix int_nat_eq nrows nrows_le of_nat_le_iff)
lemma ncols_move_matrix_le: "ncols (move_matrix A j i) ≤ nat((int (ncols A)) + i)"
by (metis nrows_move_matrix_le nrows_transpose transpose_move_matrix)
lemma mult_matrix_assoc:
assumes
"∀a. fmul1 0 a = 0"
"∀a. fmul1 a 0 = 0"
"∀a. fmul2 0 a = 0"
"∀a. fmul2 a 0 = 0"
"fadd1 0 0 = 0"
"fadd2 0 0 = 0"
"∀a b c d. fadd2 (fadd1 a b) (fadd1 c d) = fadd1 (fadd2 a c) (fadd2 b d)"
"associative fadd1"
"associative fadd2"
"∀a b c. fmul2 (fmul1 a b) c = fmul1 a (fmul2 b c)"
"∀a b c. fmul2 (fadd1 a b) c = fadd1 (fmul2 a c) (fmul2 b c)"
"∀a b c. fmul1 c (fadd2 a b) = fadd2 (fmul1 c a) (fmul1 c b)"
shows "mult_matrix fmul2 fadd2 (mult_matrix fmul1 fadd1 A B) C = mult_matrix fmul1 fadd1 A (mult_matrix fmul2 fadd2 B C)"
proof -
have comb_left: "!! A B x y. A = B ⟹ (Rep_matrix (Abs_matrix A)) x y = (Rep_matrix(Abs_matrix B)) x y" by blast
have fmul2fadd1fold: "!! x s n. fmul2 (foldseq fadd1 s n) x = foldseq fadd1 (λk. fmul2 (s k) x) n"
by (rule_tac g1 = "λy. fmul2 y x" in ssubst [OF foldseq_distr_unary], insert assms, simp_all)
have fmul1fadd2fold: "!! x s n. fmul1 x (foldseq fadd2 s n) = foldseq fadd2 (λk. fmul1 x (s k)) n"
using assms by (rule_tac g1 = "λy. fmul1 x y" in ssubst [OF foldseq_distr_unary], simp_all)
let ?N = "max (ncols A) (max (ncols B) (max (nrows B) (nrows C)))"
show ?thesis
apply (intro matrix_eqI)
apply (simp add: mult_matrix_def)
apply (simplesubst mult_matrix_nm[of _ "max (ncols (mult_matrix_n (max (ncols A) (nrows B)) fmul1 fadd1 A B)) (nrows C)" _ "max (ncols B) (nrows C)"])
apply (simp add: max1 max2 mult_n_ncols mult_n_nrows assms)+
apply (simplesubst mult_matrix_nm[of _ "max (ncols A) (nrows (mult_matrix_n (max (ncols B) (nrows C)) fmul2 fadd2 B C))" _ "max (ncols A) (nrows B)"])
apply (simp add: max1 max2 mult_n_ncols mult_n_nrows assms)+
apply (simplesubst mult_matrix_nm[of _ _ _ "?N"])
apply (simp add: max1 max2 mult_n_ncols mult_n_nrows assms)+
apply (simplesubst mult_matrix_nm[of _ _ _ "?N"])
apply (simp add: max1 max2 mult_n_ncols mult_n_nrows assms)+
apply (simplesubst mult_matrix_nm[of _ _ _ "?N"])
apply (simp add: max1 max2 mult_n_ncols mult_n_nrows assms)+
apply (simplesubst mult_matrix_nm[of _ _ _ "?N"])
apply (simp add: max1 max2 mult_n_ncols mult_n_nrows assms)+
apply (simp add: mult_matrix_n_def)
apply (rule comb_left)
apply ((rule ext)+, simp)
apply (simplesubst RepAbs_matrix)
apply (rule exI[of _ "nrows B"])
apply (simp add: nrows assms foldseq_zero)
apply (rule exI[of _ "ncols C"])
apply (simp add: assms ncols foldseq_zero)
apply (subst RepAbs_matrix)
apply (rule exI[of _ "nrows A"])
apply (simp add: nrows assms foldseq_zero)
apply (rule exI[of _ "ncols B"])
apply (simp add: assms ncols foldseq_zero)
apply (simp add: fmul2fadd1fold fmul1fadd2fold assms)
apply (subst foldseq_foldseq)
apply (simp add: assms)+
apply (simp add: transpose_infmatrix)
done
qed
lemma mult_matrix_assoc_simple:
assumes
"∀a. fmul 0 a = 0"
"∀a. fmul a 0 = 0"
"associative fadd"
"commutative fadd"
"associative fmul"
"distributive fmul fadd"
shows "mult_matrix fmul fadd (mult_matrix fmul fadd A B) C = mult_matrix fmul fadd A (mult_matrix fmul fadd B C)"
by (smt (verit) assms associative_def commutative_def distributive_def l_distributive_def mult_matrix_assoc r_distributive_def)
lemma transpose_apply_matrix: "f 0 = 0 ⟹ transpose_matrix (apply_matrix f A) = apply_matrix f (transpose_matrix A)"
by (simp add: matrix_eqI)
lemma transpose_combine_matrix: "f 0 0 = 0 ⟹ transpose_matrix (combine_matrix f A B) = combine_matrix f (transpose_matrix A) (transpose_matrix B)"
by (simp add: matrix_eqI)
lemma Rep_mult_matrix:
assumes "∀a. fmul 0 a = 0" "∀a. fmul a 0 = 0" "fadd 0 0 = 0"
shows
"Rep_matrix(mult_matrix fmul fadd A B) j i =
foldseq fadd (λk. fmul (Rep_matrix A j k) (Rep_matrix B k i)) (max (ncols A) (nrows B))"
using assms
apply (simp add: mult_matrix_def mult_matrix_n_def)
apply (subst RepAbs_matrix)
apply (rule exI[of _ "nrows A"], simp add: nrows foldseq_zero)
apply (rule exI[of _ "ncols B"], simp add: ncols foldseq_zero)
apply simp
done
lemma transpose_mult_matrix:
assumes
"∀a. fmul 0 a = 0"
"∀a. fmul a 0 = 0"
"fadd 0 0 = 0"
"∀x y. fmul y x = fmul x y"
shows
"transpose_matrix (mult_matrix fmul fadd A B) = mult_matrix fmul fadd (transpose_matrix B) (transpose_matrix A)"
using assms
by (simp add: matrix_eqI Rep_mult_matrix ac_simps)
lemma column_transpose_matrix: "column_of_matrix (transpose_matrix A) n = transpose_matrix (row_of_matrix A n)"
by (simp add: matrix_eqI)
lemma take_columns_transpose_matrix: "take_columns (transpose_matrix A) n = transpose_matrix (take_rows A n)"
by (simp add: matrix_eqI)
instantiation matrix :: ("{zero, ord}") ord
begin
definition
le_matrix_def: "A ≤ B ⟷ (∀j i. Rep_matrix A j i ≤ Rep_matrix B j i)"
definition
less_def: "A < (B::'a matrix) ⟷ A ≤ B ∧ ¬ B ≤ A"
instance ..
end
instance matrix :: ("{zero, order}") order
proof
fix x y z :: "'a matrix"
assume "x ≤ y" "y ≤ z"
show "x ≤ z"
by (meson ‹x ≤ y› ‹y ≤ z› le_matrix_def order_trans)
next
fix x y :: "'a matrix"
assume "x ≤ y" "y ≤ x"
show "x = y"
by (meson ‹x ≤ y› ‹y ≤ x› le_matrix_def matrix_eqI order_antisym)
qed (auto simp: less_def le_matrix_def)
lemma le_apply_matrix:
assumes
"f 0 = 0"
"∀x y. x ≤ y ⟶ f x ≤ f y"
"(a::('a::{ord, zero}) matrix) ≤ b"
shows "apply_matrix f a ≤ apply_matrix f b"
using assms by (simp add: le_matrix_def)
lemma le_combine_matrix:
assumes
"f 0 0 = 0"
"∀a b c d. a ≤ b ∧ c ≤ d ⟶ f a c ≤ f b d"
"A ≤ B"
"C ≤ D"
shows "combine_matrix f A C ≤ combine_matrix f B D"
using assms by (simp add: le_matrix_def)
lemma le_left_combine_matrix:
assumes
"f 0 0 = 0"
"∀a b c. a ≤ b ⟶ f c a ≤ f c b"
"A ≤ B"
shows "combine_matrix f C A ≤ combine_matrix f C B"
using assms by (simp add: le_matrix_def)
lemma le_right_combine_matrix:
assumes
"f 0 0 = 0"
"∀a b c. a ≤ b ⟶ f a c ≤ f b c"
"A ≤ B"
shows "combine_matrix f A C ≤ combine_matrix f B C"
using assms by (simp add: le_matrix_def)
lemma le_transpose_matrix: "(A ≤ B) = (transpose_matrix A ≤ transpose_matrix B)"
by (simp add: le_matrix_def, auto)
lemma le_foldseq:
assumes
"∀a b c d . a ≤ b ∧ c ≤ d ⟶ f a c ≤ f b d"
"∀i. i ≤ n ⟶ s i ≤ t i"
shows "foldseq f s n ≤ foldseq f t n"
proof -
have "∀s t. (∀i. i<=n ⟶ s i ≤ t i) ⟶ foldseq f s n ≤ foldseq f t n"
by (induct n) (simp_all add: assms)
then show "foldseq f s n ≤ foldseq f t n" using assms by simp
qed
lemma le_left_mult:
assumes
"∀a b c d. a ≤ b ∧ c ≤ d ⟶ fadd a c ≤ fadd b d"
"∀c a b. 0 ≤ c ∧ a ≤ b ⟶ fmul c a ≤ fmul c b"
"∀a. fmul 0 a = 0"
"∀a. fmul a 0 = 0"
"fadd 0 0 = 0"
"0 ≤ C"
"A ≤ B"
shows "mult_matrix fmul fadd C A ≤ mult_matrix fmul fadd C B"
using assms
apply (auto simp: le_matrix_def Rep_mult_matrix)
apply (simplesubst foldseq_zerotail[of _ _ _ "max (ncols C) (max (nrows A) (nrows B))"], simp_all add: nrows ncols max1 max2)+
apply (rule le_foldseq)
apply (auto)
done
lemma le_right_mult:
assumes
"∀a b c d. a ≤ b ∧ c ≤ d ⟶ fadd a c ≤ fadd b d"
"∀c a b. 0 ≤ c ∧ a ≤ b ⟶ fmul a c ≤ fmul b c"
"∀a. fmul 0 a = 0"
"∀a. fmul a 0 = 0"
"fadd 0 0 = 0"
"0 ≤ C"
"A ≤ B"
shows "mult_matrix fmul fadd A C ≤ mult_matrix fmul fadd B C"
using assms
apply (auto simp: le_matrix_def Rep_mult_matrix)
apply (simplesubst foldseq_zerotail[of _ _ _ "max (nrows C) (max (ncols A) (ncols B))"], simp_all add: nrows ncols max1 max2)+
apply (rule le_foldseq)
apply (auto)
done
lemma spec2: "∀j i. P j i ⟹ P j i" by blast
lemma singleton_matrix_le[simp]: "(singleton_matrix j i a ≤ singleton_matrix j i b) = (a ≤ (b::_::order))"
by (auto simp: le_matrix_def)
lemma singleton_le_zero[simp]: "(singleton_matrix j i x ≤ 0) = (x ≤ (0::'a::{order,zero}))"
by (metis singleton_matrix_le singleton_matrix_zero)
lemma singleton_ge_zero[simp]: "(0 ≤ singleton_matrix j i x) = ((0::'a::{order,zero}) ≤ x)"
by (metis singleton_matrix_le singleton_matrix_zero)
lemma move_matrix_le_zero[simp]:
fixes A:: "'a::{order,zero} matrix"
assumes "0 ≤ j" "0 ≤ i"
shows "(move_matrix A j i ≤ 0) = (A ≤ 0)"
proof -
have "Rep_matrix A j' i' ≤ 0"
if "∀n m. ¬ int n < j ∧ ¬ int m < i ⟶ Rep_matrix A (nat (int n - j)) (nat (int m - i)) ≤ 0"
for j' i'
using that[rule_format, of "j' + nat j" "i' + nat i"] by (simp add: assms)
then show ?thesis
by (auto simp: le_matrix_def)
qed
lemma move_matrix_zero_le[simp]:
fixes A:: "'a::{order,zero} matrix"
assumes "0 ≤ j" "0 ≤ i"
shows "(0 ≤ move_matrix A j i) = (0 ≤ A)"
proof -
have "0 ≤ Rep_matrix A j' i'"
if "∀n m. ¬ int n < j ∧ ¬ int m < i ⟶ 0 ≤ Rep_matrix A (nat (int n - j)) (nat (int m - i))"
for j' i'
using that[rule_format, of "j' + nat j" "i' + nat i"] by (simp add: assms)
then show ?thesis
by (auto simp: le_matrix_def)
qed
lemma move_matrix_le_move_matrix_iff[simp]:
fixes A:: "'a::{order,zero} matrix"
assumes "0 ≤ j" "0 ≤ i"
shows "(move_matrix A j i ≤ move_matrix B j i) = (A ≤ B)"
proof -
have "Rep_matrix A j' i' ≤ Rep_matrix B j' i'"
if "∀n m. ¬ int n < j ∧ ¬ int m < i ⟶ Rep_matrix A (nat (int n - j)) (nat (int m - i)) ≤ Rep_matrix B (nat (int n - j)) (nat (int m - i))"
for j' i'
using that[rule_format, of "j' + nat j" "i' + nat i"] by (simp add: assms)
then show ?thesis
by (auto simp: le_matrix_def)
qed
instantiation matrix :: ("{lattice, zero}") lattice
begin
definition "inf = combine_matrix inf"
definition "sup = combine_matrix sup"
instance
by standard (auto simp: le_infI le_matrix_def inf_matrix_def sup_matrix_def)
end
instantiation matrix :: ("{plus, zero}") plus
begin
definition
plus_matrix_def: "A + B = combine_matrix (+) A B"
instance ..
end
instantiation matrix :: ("{uminus, zero}") uminus
begin
definition
minus_matrix_def: "- A = apply_matrix uminus A"
instance ..
end
instantiation matrix :: ("{minus, zero}") minus
begin
definition
diff_matrix_def: "A - B = combine_matrix (-) A B"
instance ..
end
instantiation matrix :: ("{plus, times, zero}") times
begin
definition
times_matrix_def: "A * B = mult_matrix ((*)) (+) A B"
instance ..
end
instantiation matrix :: ("{lattice, uminus, zero}") abs
begin
definition
abs_matrix_def: "¦A :: 'a matrix¦ = sup A (- A)"
instance ..
end
instance matrix :: (monoid_add) monoid_add
proof
fix A B C :: "'a matrix"
show "A + B + C = A + (B + C)"
by (simp add: add.assoc matrix_eqI plus_matrix_def)
show "0 + A = A"
by (simp add: matrix_eqI plus_matrix_def)
show "A + 0 = A"
by (simp add: matrix_eqI plus_matrix_def)
qed
instance matrix :: (comm_monoid_add) comm_monoid_add
proof
fix A B :: "'a matrix"
show "A + B = B + A"
by (simp add: add.commute matrix_eqI plus_matrix_def)
show "0 + A = A"
by (simp add: plus_matrix_def matrix_eqI)
qed
instance matrix :: (group_add) group_add
proof
fix A B :: "'a matrix"
show "- A + A = 0"
by (simp add: plus_matrix_def minus_matrix_def matrix_eqI)
show "A + - B = A - B"
by (simp add: plus_matrix_def diff_matrix_def minus_matrix_def matrix_eqI)
qed
instance matrix :: (ab_group_add) ab_group_add
proof
fix A B :: "'a matrix"
show "- A + A = 0"
by (simp add: plus_matrix_def minus_matrix_def matrix_eqI)
show "A - B = A + - B"
by (simp add: plus_matrix_def diff_matrix_def minus_matrix_def matrix_eqI)
qed
instance matrix :: (ordered_ab_group_add) ordered_ab_group_add
proof
fix A B C :: "'a matrix"
assume "A ≤ B"
then show "C + A ≤ C + B"
by (simp add: le_matrix_def plus_matrix_def)
qed
instance matrix :: (lattice_ab_group_add) semilattice_inf_ab_group_add ..
instance matrix :: (lattice_ab_group_add) semilattice_sup_ab_group_add ..
instance matrix :: (semiring_0) semiring_0
proof
fix A B C :: "'a matrix"
show "A * B * C = A * (B * C)"
unfolding times_matrix_def
by (smt (verit, best) add.assoc associative_def distrib_left distrib_right group_cancel.add2 mult.assoc mult_matrix_assoc mult_not_zero)
show "(A + B) * C = A * C + B * C"
unfolding times_matrix_def plus_matrix_def
using l_distributive_matrix
by (metis (full_types) add.assoc add.commute associative_def commutative_def distrib_right l_distributive_def mult_not_zero)
show "A * (B + C) = A * B + A * C"
unfolding times_matrix_def plus_matrix_def
using r_distributive_matrix
by (metis (no_types, lifting) add.assoc add.commute associative_def commutative_def distrib_left mult_zero_left mult_zero_right r_distributive_def)
qed (auto simp: times_matrix_def)
instance matrix :: (ring) ring ..
instance matrix :: (ordered_ring) ordered_ring
proof
fix A B C :: "'a matrix"
assume §: "A ≤ B" "0 ≤ C"
from § show "C * A ≤ C * B"
by (simp add: times_matrix_def add_mono le_left_mult mult_left_mono)
from § show "A * C ≤ B * C"
by (simp add: times_matrix_def add_mono le_right_mult mult_right_mono)
qed
instance matrix :: (lattice_ring) lattice_ring
proof
fix A B C :: "('a :: lattice_ring) matrix"
show "¦A¦ = sup A (-A)"
by (simp add: abs_matrix_def)
qed
instance matrix :: (lattice_ab_group_add_abs) lattice_ab_group_add_abs
proof
show "⋀a:: 'a matrix. ¦a¦ = sup a (- a)"
by (simp add: abs_matrix_def)
qed
lemma Rep_matrix_add[simp]:
"Rep_matrix ((a::('a::monoid_add)matrix)+b) j i = (Rep_matrix a j i) + (Rep_matrix b j i)"
by (simp add: plus_matrix_def)
lemma Rep_matrix_mult: "Rep_matrix ((a::('a::semiring_0) matrix) * b) j i =
foldseq (+) (λk. (Rep_matrix a j k) * (Rep_matrix b k i)) (max (ncols a) (nrows b))"
by (simp add: times_matrix_def Rep_mult_matrix)
lemma apply_matrix_add: "∀x y. f (x+y) = (f x) + (f y) ⟹ f 0 = (0::'a)
⟹ apply_matrix f ((a::('a::monoid_add) matrix) + b) = (apply_matrix f a) + (apply_matrix f b)"
by (simp add: matrix_eqI)
lemma singleton_matrix_add: "singleton_matrix j i ((a::_::monoid_add)+b) = (singleton_matrix j i a) + (singleton_matrix j i b)"
by (simp add: matrix_eqI)
lemma nrows_mult: "nrows ((A::('a::semiring_0) matrix) * B) ≤ nrows A"
by (simp add: times_matrix_def mult_nrows)
lemma ncols_mult: "ncols ((A::('a::semiring_0) matrix) * B) ≤ ncols B"
by (simp add: times_matrix_def mult_ncols)
definition
one_matrix :: "nat ⇒ ('a::{zero,one}) matrix" where
"one_matrix n = Abs_matrix (λj i. if j = i ∧ j < n then 1 else 0)"
lemma Rep_one_matrix[simp]: "Rep_matrix (one_matrix n) j i = (if (j = i ∧ j < n) then 1 else 0)"
unfolding one_matrix_def
by (smt (verit, del_insts) RepAbs_matrix not_le)
lemma nrows_one_matrix[simp]: "nrows ((one_matrix n) :: ('a::zero_neq_one)matrix) = n" (is "?r = _")
proof -
have "?r ≤ n" by (simp add: nrows_le)
moreover have "n ≤ ?r" by (simp add:le_nrows, arith)
ultimately show "?r = n" by simp
qed
lemma ncols_one_matrix[simp]: "ncols ((one_matrix n) :: ('a::zero_neq_one)matrix) = n" (is "?r = _")
proof -
have "?r ≤ n" by (simp add: ncols_le)
moreover have "n ≤ ?r" by (simp add: le_ncols, arith)
ultimately show "?r = n" by simp
qed
lemma one_matrix_mult_right[simp]:
fixes A :: "('a::semiring_1) matrix"
shows "ncols A ≤ n ⟹ A * (one_matrix n) = A"
apply (intro matrix_eqI)
apply (simp add: times_matrix_def Rep_mult_matrix)
apply (subst foldseq_almostzero, auto simp: ncols)
done
lemma one_matrix_mult_left[simp]:
fixes A :: "('a::semiring_1) matrix"
shows "nrows A ≤ n ⟹ (one_matrix n) * A = A"
apply (intro matrix_eqI)
apply (simp add: times_matrix_def Rep_mult_matrix)
apply (subst foldseq_almostzero, auto simp: nrows)
done
lemma transpose_matrix_mult:
fixes A :: "('a::comm_ring) matrix"
shows "transpose_matrix (A*B) = (transpose_matrix B) * (transpose_matrix A)"
by (simp add: times_matrix_def transpose_mult_matrix mult.commute)
lemma transpose_matrix_add:
fixes A :: "('a::monoid_add) matrix"
shows "transpose_matrix (A+B) = transpose_matrix A + transpose_matrix B"
by (simp add: plus_matrix_def transpose_combine_matrix)
lemma transpose_matrix_diff:
fixes A :: "('a::group_add) matrix"
shows "transpose_matrix (A-B) = transpose_matrix A - transpose_matrix B"
by (simp add: diff_matrix_def transpose_combine_matrix)
lemma transpose_matrix_minus:
fixes A :: "('a::group_add) matrix"
shows "transpose_matrix (-A) = - transpose_matrix (A::'a matrix)"
by (simp add: minus_matrix_def transpose_apply_matrix)
definition right_inverse_matrix :: "('a::{ring_1}) matrix ⇒ 'a matrix ⇒ bool" where
"right_inverse_matrix A X == (A * X = one_matrix (max (nrows A) (ncols X))) ∧ nrows X ≤ ncols A"
definition left_inverse_matrix :: "('a::{ring_1}) matrix ⇒ 'a matrix ⇒ bool" where
"left_inverse_matrix A X == (X * A = one_matrix (max(nrows X) (ncols A))) ∧ ncols X ≤ nrows A"
definition inverse_matrix :: "('a::{ring_1}) matrix ⇒ 'a matrix ⇒ bool" where
"inverse_matrix A X == (right_inverse_matrix A X) ∧ (left_inverse_matrix A X)"
lemma right_inverse_matrix_dim: "right_inverse_matrix A X ⟹ nrows A = ncols X"
using ncols_mult[of A X] nrows_mult[of A X]
by (simp add: right_inverse_matrix_def)
lemma left_inverse_matrix_dim: "left_inverse_matrix A Y ⟹ ncols A = nrows Y"
using ncols_mult[of Y A] nrows_mult[of Y A]
by (simp add: left_inverse_matrix_def)
lemma left_right_inverse_matrix_unique:
assumes "left_inverse_matrix A Y" "right_inverse_matrix A X"
shows "X = Y"
proof -
have "Y = Y * one_matrix (nrows A)"
by (metis assms(1) left_inverse_matrix_def one_matrix_mult_right)
also have "… = Y * (A * X)"
by (metis assms(2) max.idem right_inverse_matrix_def right_inverse_matrix_dim)
also have "… = (Y * A) * X" by (simp add: mult.assoc)
also have "… = X"
using assms left_inverse_matrix_def right_inverse_matrix_def
by (metis left_inverse_matrix_dim max.idem one_matrix_mult_left)
ultimately show "X = Y" by (simp)
qed
lemma inverse_matrix_inject: "⟦ inverse_matrix A X; inverse_matrix A Y ⟧ ⟹ X = Y"
by (auto simp: inverse_matrix_def left_right_inverse_matrix_unique)
lemma one_matrix_inverse: "inverse_matrix (one_matrix n) (one_matrix n)"
by (simp add: inverse_matrix_def left_inverse_matrix_def right_inverse_matrix_def)
lemma zero_imp_mult_zero: "(a::'a::semiring_0) = 0 | b = 0 ⟹ a * b = 0"
by auto
lemma Rep_matrix_zero_imp_mult_zero:
"∀j i k. (Rep_matrix A j k = 0) | (Rep_matrix B k i) = 0 ⟹ A * B = (0::('a::lattice_ring) matrix)"
by (simp add: matrix_eqI Rep_matrix_mult foldseq_zero zero_imp_mult_zero)
lemma add_nrows: "nrows (A::('a::monoid_add) matrix) ≤ u ⟹ nrows B ≤ u ⟹ nrows (A + B) ≤ u"
by (simp add: nrows_le)
lemma move_matrix_row_mult:
fixes A :: "('a::semiring_0) matrix"
shows "move_matrix (A * B) j 0 = (move_matrix A j 0) * B"
proof -
have "⋀m. ¬ int m < j ⟹ ncols (move_matrix A j 0) ≤ max (ncols A) (nrows B)"
by (smt (verit, best) max1 nat_int ncols_move_matrix_le)
then show ?thesis
apply (intro matrix_eqI)
apply (auto simp: Rep_matrix_mult foldseq_zero)
apply (rule_tac foldseq_zerotail[symmetric])
apply (auto simp: nrows zero_imp_mult_zero max2)
done
qed
lemma move_matrix_col_mult:
fixes A :: "('a::semiring_0) matrix"
shows "move_matrix (A * B) 0 i = A * (move_matrix B 0 i)"
proof -
have "⋀n. ¬ int n < i ⟹ nrows (move_matrix B 0 i) ≤ max (ncols A) (nrows B)"
by (smt (verit, del_insts) max2 nat_int nrows_move_matrix_le)
then show ?thesis
apply (intro matrix_eqI)
apply (auto simp: Rep_matrix_mult foldseq_zero)
apply (rule_tac foldseq_zerotail[symmetric])
apply (auto simp: ncols zero_imp_mult_zero max1)
done
qed
lemma move_matrix_add: "((move_matrix (A + B) j i)::(('a::monoid_add) matrix)) = (move_matrix A j i) + (move_matrix B j i)"
by (simp add: matrix_eqI)
lemma move_matrix_mult: "move_matrix ((A::('a::semiring_0) matrix)*B) j i = (move_matrix A j 0) * (move_matrix B 0 i)"
by (simp add: move_matrix_ortho[of "A*B"] move_matrix_col_mult move_matrix_row_mult)
definition scalar_mult :: "('a::ring) ⇒ 'a matrix ⇒ 'a matrix" where
"scalar_mult a m == apply_matrix ((*) a) m"
lemma scalar_mult_zero[simp]: "scalar_mult y 0 = 0"
by (simp add: scalar_mult_def)
lemma scalar_mult_add: "scalar_mult y (a+b) = (scalar_mult y a) + (scalar_mult y b)"
by (simp add: scalar_mult_def apply_matrix_add algebra_simps)
lemma Rep_scalar_mult[simp]: "Rep_matrix (scalar_mult y a) j i = y * (Rep_matrix a j i)"
by (simp add: scalar_mult_def)
lemma scalar_mult_singleton[simp]: "scalar_mult y (singleton_matrix j i x) = singleton_matrix j i (y * x)"
by (simp add: scalar_mult_def)
lemma Rep_minus[simp]: "Rep_matrix (-(A::_::group_add)) x y = - (Rep_matrix A x y)"
by (simp add: minus_matrix_def)
lemma Rep_abs[simp]: "Rep_matrix ¦A::_::lattice_ab_group_add¦ x y = ¦Rep_matrix A x y¦"
by (simp add: abs_lattice sup_matrix_def)
end